OPTIMIZING HOUSE YARDS WITH VEGETABLE CULTIVATION AS AN ALTERNATIVE FOOD IN RURAL AREAS: OPTIMALISASI PEKARANGAN RUMAH DENGAN BUDIDAYA SAYURAN SEBAGAI ALTERNATIF PANGAN DI PEDESAAN - Putro, Tetuko Rawidyo; Sistriatmaja, Muhammad Bagus; Hakim, Lukman; Rahayu, Siti Aisyah Tri; Mulyanto, Mulyanto; Sumantyo, Riwi; Purnama, Muhammad Yusuf Indra; Nugroho, Hery Sulistio Jati (Darmabakti Cendekia: Journal of Community Service and Engagements, 2025)
Background: Food security and economic empowerment of rural communities are significant challenges for sustainable development. Using the yard for vegetable cultivation can increase food availability, reduce dependence on external food sources, and improve improve the economic welfare of the community. Objective: This community service activity aims to enhance participants' skills in food production, family income, and both technical (hard skills) and social (soft skills) aspects through the use of house yards. Method: The study was conducted in Sumber Village, Sumber District, Rembang Regency, in August 2024 - February 2025. The methods include socialization, training, mentoring, and evaluation. Data were collected through observation, interviews, and pre-tests and post-tests of program participants. Results: The program's implementation showed a 40% increase in vegetable production over six months. The pre-test and post-test evaluations indicated a significant increase in hard skills (cultivation techniques and use of organic fertilizers) by 35%, and soft skills (communication and cooperation) by 30%. Conclusion: This program has proven to improve food security, family income, and community skills. This model can be replicated in other areas with a similar approach, and advanced strategies for program sustainability are needed.